(untitled) (International journal of medical sciences, 2026)
Acute appendicitis is one of the most common causes of abdominal pain requiring surgical intervention in children. Its diagnosis remains challenging due to variable clinical presentations and the potential for rapid progression to complications. This study investigates the clinical features, diagnostic methods, and treatment outcomes of pediatric patients with acute appendicitis admitted to a tertiary hospital.